The Importance of Functional Fitness in Athlete Training - Inomov Fahriddin Ormonjonovich (American Journal of Bioscience and Clinical Integrity, 2026)
This article examines the significance of functional fitness in the modern system of athlete training. It analyzes the growing role of sports science in optimizing training methodologies and highlights the increasing demands placed on athletes due to intensified competition and higher performance standards. The concept of functional fitness is defined as a comprehensive characteristic of the body’s life-support systems that ensure energy supply, metabolic regulation, adaptation, and recovery during training and competition. The structural components of functional fitness, including cardiovascular, respiratory, nervous, endocrine, immune, digestive, and excretory systems, are discussed. The article also outlines key indicators and testing methods used to assess athletes’ functional capacities. It is emphasized that a high level of functional fitness enhances competitive readiness, improves performance outcomes, and reduces the risk of injury and disease. The development and scientific substantiation of functional training approaches are identified as essential conditions for preparing highly qualified athletes.